2015
DOI: 10.12806/v14/i2/r11
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Canadian Student Leadership Practices

Abstract: Over a period of three years (2006-2008) students entering [university] were asked to complete the Student Leadership Practices Inventory (S-LPI), and 2,855 initial responses were received. Responding students were asked to complete the S-LPI again at the end of their first and third years of study. No significant differences were found in student use of the leadership practices based on age, geographic origin, or whether the student lived on or off campus during his or her first year. Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(38 reference statements)
0
8
0
3
Order By: Relevance
“…In addition, a somewhat limited range of demographic categories was considered in this study; age being a good example, as some research has shown that student leaders engage more frequently in college than they do in high school (Posner, 2013). Moreover, little is known about the actual leadership roles or experiences of the students involved in this study, only how many opportunities they had to lead and be involved (Posner, Crawford, & Denniston-Stewart, 2015). Additionally, having objective rather than subjective outcome measures (or even more than one subjective measure) would be another contribution from future scholars to better document the impact of feedback-seeking by student leaders on the behavior and sentiments of their followers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a somewhat limited range of demographic categories was considered in this study; age being a good example, as some research has shown that student leaders engage more frequently in college than they do in high school (Posner, 2013). Moreover, little is known about the actual leadership roles or experiences of the students involved in this study, only how many opportunities they had to lead and be involved (Posner, Crawford, & Denniston-Stewart, 2015). Additionally, having objective rather than subjective outcome measures (or even more than one subjective measure) would be another contribution from future scholars to better document the impact of feedback-seeking by student leaders on the behavior and sentiments of their followers.…”
Section: Discussionmentioning
confidence: 99%
“…Para pemuda harus terus belajar dan membekali diri dengan mengadopsi cara-cara baru dengan selalu melakukan inovasi dan sanggup mengkomunikasikan gagasannya (Publik, 2021). Berkaitan dengan hal tersebut, beberapa keterampilan yang dapat dikembangkan antara lain adalah kemampuan berbicara di depan publik (public speaking skills), kemampuan menganalisis dan mengambil keputusan (analysing and decision making), dan keterampilan teknis lain seperti memimpin rapat, mengelola sumber daya, dan lain-lain (Konuk & Posner, 2021). Seorang pemimpin dituntut terampil berbicara di depan publik untuk menyampaikan gagasan, mengkomunikasikan pencapaian organisasi.…”
Section: A Latar Belakangunclassified
“…The originality of this article is in generating important (Grabsch & Moore, 2021), needs (Schuleigh et al, 2021), and application to real situations (Konuk & Posner, 2021). Global leadership competencies like intercultural understanding have also been suggested as of high importance to contemporary leadership education programs' success (Armstrong, 2020;Semali & Buchko, 2014).…”
Section: Recommendations and Implicationsmentioning
confidence: 99%